Double resonance ejection using novel radiofrequency phase tracking circuitry in a miniaturized planar linear ion trap mass spectrometer. (6th November 2018) - Decker, Trevor K.; Zheng, Yajun; McClellan, Joshua S.; Ruben, Aaron J.; Lammert, Stephen A.; Austin, Daniel E.; Hawkins, Aaron R.
Abstract : Rationale: Ion trap mass spectrometers are attractive due to their inherent sensitivity and specificity. Miniaturization increases trap portability for in situ mass analysis by relaxing vacuum and voltage requirements but decreases the trapping volume. To overcome signal/resolution loss from miniaturization, double resonance ejection using phase tracking circuitry was investigated. Methods: Phase tracking circuitry was developed to induce double resonance ejection in a planar linear ion trap using the β 2/3 hexapole resonance line. Results: Double resonance was observed using phase tracking circuitry. Resolution of 0.5 m/z units and improved signal‐to‐noise ratio (SNR) compared with AC resonant ejection were achieved. Conclusions: The phase tracking circuitry proved effective despite deviations from a true phase locked condition. Double resonance ejection is a means to increase signal intensity in a miniaturized planar ion trap.